Fatigue in transportation: NTSB investigations and safety recommendations - Marcus, Jeffrey H; Rosekind, Mark R (Injury prevention, 2017)
ObjectiveWe aim to place into the scientific literature information on the prevalence of operator fatigue as a factor in causing transportation mishaps, and the categories of improvements identified to address fatigue in transportation.MethodsWe analyzed the number of major National Transportation Safety Board (NTSB) investigations that identified fatigue as a probable cause, contributing factor, or a finding. We divided all NTSB recommendations addressing fatigue issued since the agency was founded into 7 subject categories, and placed each recommendation into the appropriate category. This information was then analyzed to determine the number of recommendations in each category, both overall and by transportation mode. Analysis was also performed regarding the types of organizations that received the recommendations, whether the recommended actions have been taken, and the NTSB's evaluation of whether the action taken satisfied a given recommendation.ResultsWe reviewed 182 major NTSB investigations completed between 1 January 2001 and 31 December 2012 and found that 20% of these investigations identified fatigue as a probable cause, contributing factor, or a finding. The presence of fatigue varied between among the modes of transportation, ranging from 40% of highway investigations to 4% of marine investigations. The first NTSB recommendation to address the safety risks associated with human fatigue was issued over 40 years ago, in 1972. Since then, the NTSB has issued 205 separate fatigue-specific recommendations. Scheduling policies and practices was the most common subject category accounting for 40% of all recommendations issued. Federal agencies received 54% of all recommendations, with 22% to transportation operators, and 16% to associations. Of all NTSB fatigue recommendations, 24% were open ranging from a low of 9% in highway to 39% in aviation. Overall, only 3% of open recommendations were classified “unacceptable,” whereas 16% of all closed recommendations were classified “unacceptable.”ConclusionsAlthough there has been over 100 years of progress in recognizing and addressing the safety risk posed by human fatigue in transportation, 20% of recent NTSB investigations have identified fatigue as a probable cause, contributing factor or finding. This analysis represents the first-ever examination of fatigue identified in major NTSB investigations across modes and of the focus, recipients, and classification status of fatigue-related safety recommendations. It demonstrates that fatigue remains a significant transportation safety risk.